Molecular data support monophyly of the recently erected Riggenbachiella (Cestoda: Proteocephalidae), parasites of Neotropical catfishes - Alves, Philippe V.; Kuchta, Roman; Scholz, Tomáš (Zootaxa, 2019)
Proteocephalid tapeworms (Cestoda) are one of the dominant groups of intestinal parasites of Neotropical catfishes (Siluriformes), especially pimelodids (de Chambrier et al. 2015). The long and convoluted taxonomic history of species of Chambriella Rego, Chubb & Pavanelli, 1999 has been disentangled only recently by Alves et al. (2017). These authors erected a new genus, Riggenbachiella Alves, de Chambrier, Luque & Scholz, 2017, to accommodate R. amazonense Alves, de Chambrier, Luque & Scholz, 2017 (type-species) and R. paranaense (Pavanelli & Rego, 1989) (previously Chambriella paranaensis), parasites of pimelodid catfishes.